Landmarks in the history of Oral and Maxillofacial Surgery in Cluj-Napoca, Romania - Rotaru, Alexandru; Bârsu, Cristian; Rotaru, Horațiu (Medicine and Pharmacy Reports, 2020)
At the anniversary of a century since the establishment of medical higher education in the Romanian language, the authors present the personalities who shaped the future of dental surgery within the specialty of dental medicine, and then of the oral and maxillofacial surgery as a branch of stomatology, followed by the establishment of surgery as its own specialty and discipline. The evolutionary stages, difficulties and successes achieved by this specialty are presented through the various historical landmarks of the last century.